The Impact of Perspective Taking on Obesity Stereotypes: The Dual Mediating Effects of Self-Other Overlap and Empathy - Wu, Yunlong; Zhang, Yuzhu (Frontiers in Psychology, 2021)
Previous studies indicated that obese people face severe prejudice and discrimination in many forms because of obese stereotype and weight stigma, such as educational settings, interpersonal relationships and employment settings. However, research aimed at reducing obese stereotypes is relatively rare, and existing research has focused primarily on negative stereotypes. Based on the empathy-altruism hypothesis and self-other overlap hypothesis, the present study investigated the impact of perspective taking on both positive and negative obesity stereotypes and examined its mechanism, namely, the mediating effects of empathy and self-other overlap. A sample of 687 university students (191 males and 496 females) from China participated in this study. They completed self-report questionnaires gathering trait tendency and evaluation towards obese people. Structural equation models analysis and Bootstrap method revealed that self-other overlap mediated the relationship between perspective taking and negative obesity stereotypes, yet empathy failed to realize this. Perspective taking could improve positive obesity stereotypes through the mediating effects of self-other overlap and empathy simultaneously. Besides, through exploratory analysis, a new sequential mediating path from perspective taking to self-other overlap to empathy to positive obesity stereotypes was found. These findings address the importance of perspective taking in improving positive and negative obesity stereotypes because perspective taking promotes merging in cognition and produces empathy concern in emotion.